The effect of an eye health promotion program on the health protective behaviors of primary school students - Nukhet Kirag; Ayla Bayik Temel (Wolters Kluwer Medknow Publications, 2018)
Introduction: Undiagnosed and uncorrected refractive errors in childhood can negatively affect the development of vision and cause students to have low academic success and even quit school before graduation. This study aims to determine the effects of an eye health promotion program on the health protective behaviors of primary school students. Materials and Methods: This experimental study using a pretest-posttest design with a control group was conducted in three public primary schools in Aydın, a city in the Western Anatolia Region of Turkey, between April and November 2014. The eye health promotion program was provided by the researchers to the experimental Group 2 days in 4 weeks. The data were analyzed using the t-test, Chi-square analysis, the Mann-Whitney U-test, the Wilcoxon signed-rank test, and the McNemar test. Results: The average age of the students was identified as 9.0 ± 3.64 years. The students wearing glasses all in the experimental group and 53.3% in the control group were found to always wear their glasses after the education program was completed (P < 0.05). These students, 97.9% in the experimental group and 58.1% in the control group underwent eye examinations from an ophthalmologist (P < 0.05). The eye health protective behaviors of the experimental group were found to have positively changed in the final follow-up, compared to the control group (P < 0.05). Conclusion: The eye health promotion program was found to be effective in improving eye health protective behaviors within the experimental group.